Cardio-Pulmonary Stethoscope: Clinical Validation With Heart Failure and Hemodialysis Patients - Iskander, Magdy F.; Seto, Todd B.; Perron, Ruthsenne RG; Lim, Eunjung; Qazi, Farhan (IEEE transactions on biomedical engineering, 2018)
Objective: The purpose of this study is to evaluate the accuracy of a noninvasive radiofrequency-based device, the Cardio-Pulmonary Stethoscope (CPS), to monitor heart and respiration rates, and detect changes in lung water content in human experiments and clinical trials. Methods: Three human populations (healthy subjects (n = 4), heart failure (n = 12), and hemodialysis (n = 13) patients) were enrolled in this study. The study was conducted at the University of Hawaii and the Queen's Medical Center in Honolulu, HI, USA. Measurement of heart and respiration rates for all patients was compared with standard FDA - approved monitoring methods. For lung water measurements, CPS data were compared with simultaneous pulmonary capillary wedge pressure (PCWP) measurements for heart failure patients, and with change in weight of extracted fluid for hemodialysis patients. Results: Statistical correlation methods (Pearson, mixed, and intraclass) were used to compare the data and examine accuracy of CPS results. Results show that heart and respiration rates of all patients have excellent correlation factors, r≥0.9. Comparisons with fluid removed during hemodialysis treatment showed correlation factor of r = 0.82 to 1, while PCWP measurements of heart failure patients had correlation factor of r = 0.52 to 0.97. Conclusion: These results suggest that CPS technology accurately quantifies heart and respiration rates and measure fluid changes in the lungs. Significance: The CPS has the potential to accurately monitor lung fluid status noninvasively and continuously in a clinical and outpatient setting. Early and efficient management of lung fluid status is key in managing chronic conditions such heart failure, pulmonary hypertension, and acute respiration distress syndrome.